1992
DOI: 10.1111/j.1600-0528.1992.tb00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries, sugar consumption and restorative dental care in12–13‐year‐old children in Riyadh, Saudi Arabia

Abstract: A 3-day dietary history was obtained from 363 Riyadh schoolchildren aged 12-13 yr, after which their dentitions were examined for dental caries. About 16-31% of the children were caries-free and the mean DMFT varied between 1.67 and 2.43. However, in those with at least one tooth decayed, missing or filled, the mean DMFT remained constant at about 3, irrespective of age or gender; and most of the carious teeth were unrestored. There was a statistically significant relationship between DFS and the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 13 publications
6
41
0
1
Order By: Relevance
“…Many previous studies in Saudi among children have reported decay [dt] as the major component of dmft score. [15][16][17][18] This is a similar finding in the current study in which the [dt] accounted for 68.37% of the dmft score. The proportion of children with active caries was 77.87%, and most of the decayed teeth were unrestored; children with at least one filling (n = 3,234; 18.08%).…”
supporting
confidence: 77%
“…Many previous studies in Saudi among children have reported decay [dt] as the major component of dmft score. [15][16][17][18] This is a similar finding in the current study in which the [dt] accounted for 68.37% of the dmft score. The proportion of children with active caries was 77.87%, and most of the decayed teeth were unrestored; children with at least one filling (n = 3,234; 18.08%).…”
supporting
confidence: 77%
“…Previous analysis showed that the quality of the present consumption data decreased after seven days: the average number of snacks was 21% lower in the second week with respect to the first, probably due to some degree of tiredness of subjects 7 . As performed by other authors 14 , only the first week of the survey was therefore considered in the present investigation.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…AlSekait and Al-Nasser examined a sample of 7040 primary school children from urban and rural schools in Riyadh, revealing a dental caries prevalence of 52% and a Decayed-Missed-Filled-Teeth (DMFT) index score of 2.0 [28]. Akpata and Al-Shammery examined all 12 and 13 year old students in 10 randomly selected Riyadh schools (5 boys' schools and 5 girls' schools) and found that the dental caries prevalence was between 55.5% (for 13-year-old boys) and 73.1% (for 12-year-old girls) [29]. A study was conducted in 1999 to assess the dental caries prevalence among 12-13 year old children in 10 of the 13 administrative regions in Saudi Arabia.…”
Section: Dental Caries In Saudi Arabiamentioning
confidence: 99%